The application of ethnodrama with female adolescents under youth protection within a creative arts therapies context. Issue 2 (1st October 2015) - Snow, Stephen; D'Amico, Miranda
Adolescents living under youth protection are vulnerable to stigmatization resulting from restrictive forms of group care and being labelled with derogatory epithets. Nine young women participated in art and drama therapy as well as individual interviews about their experience of living in a residential care facility. Resultant themes are presented in the form of a case vignette and a playscript (ethnodrama), which was performed for an audience of health care providers and family members. Findings indicate that this methodological approach was effective in eliciting the experiences of participants. However, while audience members indicated that the resulting performance had the intended impact, limitations in the project's design precluded efforts to fully analyse the statistical significance of their pre- and postperformance responses.